PERAN STAKEHOLDERS DALAM PENGEMBANGAN DESA WISATA GOGIK DI KABUPATEN SEMARANG - Inanda Nadhif, Nuno; Subowo, Ari; Santoso, R. Slamet (Journal of Public Policy and Management Review, 2024)
The development of tourist villages is an effective strategy to improve the welfare of local communities through optimizing local potential. Gogik Tourism Village in Semarang Regency is an example of a village whose potential is being developed. This research aims to analyze the role of various stakeholders in the development process of the tourist village. The methodology used is a qualitative approach with data collection through in-depth interviews, observation and documentation. The stakeholders involved include the Semarang Regency Tourism Office, Gogik Village Government, Village-Owned Enterprises (BUMDes), Tourism Awareness Groups (Pokdarwis), and local communities. The research results show that the role of the Semarang Regency Tourism Office is very vital in providing basic infrastructure and regulations that support the development of tourist villages. The Gogik Village Government has a proactive role in educating the community. BUMDes plays a role in preparing superior programs such as improving tourist areas, improving facilities and improving the quality of tourist villages. Pokdarwis contributes to managing facilities and organizing tourism activities as well as marketing tourist villages. Meanwhile, local communities act as supporters and provide significant contributions. This collaboration between stakeholders produces various positive impacts, such as improving the local economy, preserving culture and the environment, and increasing community capacity. However, the challenges faced include limited resources, inadequate coordination between stakeholders, and the gap between community expectations and reality on the ground. This research recommends increasing communication and cooperation between stakeholders, as well as increasing participation by implementing a comprehensive educational program for the sustainable development of the Gogik Tourist Village.